miR-125a regulates angiogenesis of gastric cancer by targeting vascular endothelial growth factor A - Jun Dai; Jinyu Wang; Lili Yang; Ying Xiao; Qiurong Ruan (2015)
A recent discovery revealed that microRNAs (miRNAs) have an essential effect in the development and progression of gastric cancer (GC). It has already been shown that miR‑125a may inhibit tumor development by targeting human epidermal growth factor receptor-2 (Her-2) in GC; however, the other roles of miR‑125a in gastric cancer remained to be explored. Our study confirmed that miR‑125a was indeed capable of modulating the expression of VEGF-A in gastric cancer cells. In vitro, low expression of miR‑125a was able to maintain the secretion of VEGF-A, while the latter increased Akt phosphorylation level in endothelial cells and thereby promoted the proliferation, migration and angiogenesis of human umbilical vein endothelial cells (HUVECs). Our investigation showed that miR‑125a expression decreased significantly in gastric cancer comparing with normal gastric tissue and was negatively correlated with the expression of VEGF-A (P<0.05). In vivo, the expression of miR‑125a was inversely proportional to microvessel density (MVD) (r=-0.5382, P<0.001). The results of this study suggested that low expression of miR‑125a predict a worse survival in gastric cancer patients. Collectively, our results indicated that miR‑125a regulated the paracrine of VEGF-A in gastric cancer and thereby controlled the angiogenesis of the tumor.